RAYLEIGH SCATTERING IN METAL NANOPARTICLES IN LIQUIDS - Dorokhov, Victor; Hauser, Yulia (Revista Inclusiones, 2020)
In this study, silver nanoparticles with narrow particle size distribution synthesized by acoustoplasma technique were studied. A number of features of stimulated thermal Rayleigh scattering (STRS) in pure liquids and suspensions of nanoparticles were investigated in this work. It is shown that the scattering efficiency is not reduced in case of wide spectral bandwidth pump radiation. It is shown experimentally that the frequency shift of the scattered signal relative to the pump frequency greatly exceeds the theoretical value. It is also shown theoretically that the frequency shift value does not depend on the linewidth of the pump